Evaluating the Effects of Fish Solubles on Nursery Pig Performance - A. M. Jones; J. C. Woodworth; M. D. Tokach; S. Herbert; J. Smith; D. Berry; R. D. Goodband; J. M. DeRouchey; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 700 barrows (Line 200 × 400, DNA, Columbus, NE; initially 14.3 lb) were used in a 21-d growth trial with 5 pigs per pen and 28 pens per treatment. Pigs were weaned at approximately 21 d of age, placed in nursery pens according to BW and fed a common pelleted starter diet for 3 d. Pigs were then weighed and pens were blocked by BW to 1 of 5 dietary treatments in a randomized complete block design. Dietary treatments included a corn-soybean meal-based control diet and 4 diets containing 6% LT Prime Menhaden Fishmeal (Daybrook Fisheries Inc., New Orleans, LA). One batch of fish meal contained 0.87% fish solubles and the second batch contained 24.35% solubles. The 2 batches were then blended to provide dietary treatments with 0.87, 8.70, 16.52, and 24.35% fish solubles. A composite sample from each batch of fish meal was collected and analyzed for AA content and proximate analysis prior to formulation to determine nutrient loading values. Dietary treatments contained 10% spray-dried whey and were formulated to contain 1.35% standardized ileal digestible Lys, and were balanced on an NE basis. Overall (d 0 to 21), pigs fed diets with fish meal had increased (P<0.05) ADG and ADFI compared to pigs fed the soybean meal-based control diet. There was no evidence for differences in growth performance with increasing fish solubles. In conclusion, the amount of fish solubles in the whole fish meal do not appear to influence nursery pig growth performance.
Keywords: fish meal; fish solubles; growth; nursery pig